Analysis of Maximum Economic Length of Soil Nail for Slope Stability - Pathak, Bhashkar (Journal of Earth and Marine Technology (JEMT), 2023)
Slope stability is of utmost importance in geotechnical engineering, necessitating effective reinforcement methods to mitigate failures. This study examined the advantages, limitations, and overall suitability of soil nails and cable anchors in stabilizing slopes. Numerical modeling and analysis were performed using the Rocscience Slide2 program. The study analyzed soil nails and cable anchors for slopes of 10 m to 60 m height, slope angle from 35° to 90°, and friction angle from 27° to 36°. The findings reveal that the maximum economic length of soil nails decreases as slip surface depth, slope height, and slope angle increase. Additionally, the friction angle of the soil has a negligible effect on the maximum economic length of the soil nail.